Exploring hand washing behavior among the students of Canadian Maple International School: Understanding knowledge attitude and practices.: Hand washing behavior among students - Mohiuddin, Zebunnesa; Shams, Shahtina; Mahbub, Tasnuva Andalib (Journal of the Medical College for Women & Hospital, 2025)
Introduction: Hand washing is the act of cleaning one’s hand with any liquid or with soap for the purpose of removing microorganism. Hand washing is a learned behavior, so it is required to learn proper hand washing as a child to lay down the fundamentals of lifelong responsibility of maintaining personal hygiene in childhood. Lack of knowledge and practice of proper hygiene increases the incidence of communicable diseases especially among school children in developing countries. Aim:This study is done to identify gaps in knowledge, poor attitudes and substandard practices in hand washing and to enhance the development of appropriate strategies to promote hand hygiene for primary and secondary school students in the future. Hand washing is key to reducing the occurrence of infectious diseases among school students . Materials and Method: The survey was cross-sectional which was conducted among the children of Canadian Maple International School during the period of August to October 2022 to assess the level of knowledge about hand washing among the school students. Sampling was done by purposive method and data was collected through face-to-face interview by using semi-structured questionnaire. After completion of data collection, statistical analysis was done using the Statistical Package for the Social Science. Study was conducted among 51 students of (8-14) years old. Result: Among 51 respondents, 49.02% were within 8-10 years of age, 35.29% were within (10-12) years of age and the rest 15.69% belonged to (12-14) age group. All of them were Muslims. About 49.01% respondents have more than 4 family members. 98% of the respondents had the habit of daily hand washing. 74.50% were aware of hands washing after handling money. 84.30% respondents washed their hands with soap water. In the midst of 51 respondent there is a significant difference in the habit of hand washing at 5% level of significance. The study reveals that more than 80% students have the knowledge about hand washing. Conclusion: Although the results of this study indicated that respondents had high levels of knowledge, attitude and practices of hand hygiene, the information provided in this study regarding current hand hygiene knowledge, attitudes and practices among students will help identify the gaps in knowledge, poor attitudes and substandard practices. This will also be valuable to the design and implementation of the hand hygiene intervention. Hand hygiene is essential to the health of the school community. This study assessed the levels of knowledge, attitude and practices of hand hygiene among Canadian Maple International School, Dhaka. J Med Coll Women Hosp.2025; 21 (2):136-143